Effects of multidirectional elastic tape on forearm muscle activity and wrist extension during submaximal gripping in individuals with lateral elbow tendinopathy: A randomised crossover trial. (December 2022) - Hill, Caitlin E.; Heales, Luke J.; Stanton, Robert; Holmes, Michael W.R.; Kean, Crystal O.
Abstract: Background: Lateral elbow tendinopathy is associated with changes to forearm muscle activity and wrist posture during gripping. Multidirectional elastic tape is thought to exert a deloading effect on underlying musculotendinous structures, which could potentially alter muscle activity or wrist posture. Methods: This single-blinded randomised crossover trial compared the immediate effects of tensioned multidirectional elastic tape, untensioned control tape, and no tape, in individuals with lateral elbow tendinopathy. Muscle activity of extensor carpi radialis longus and brevis, extensor carpi ulnaris, and extensor digitorum and wrist extension angle were recorded during a submaximal gripping task. Muscle activity was normalised to the maximum amplitude recorded during maximal grip. Change scores were calculated (post-condition minus baseline). Repeated-measure analyses of variance were used to examine between-condition differences. Findings: 27 participants (16 males, mean age (SD): 48.6 (11.9) years) underwent all conditions. Extensor digitorum muscle activity was reduced during the multidirectional elastic tape, compared to control tape and no tape (MD −5.6% [95%CI: −9.9 to −1.3], MD −5.8% [95%CI: −10.2 to −1.4], respectively). Extensor carpi ulnaris muscle activity was reduced during the multidirectional elastic tape, compared to the control tape (mean difference [MD] −3.2% [95%CI: −5.3 to −1.1]), but increased during the control tape, compared to the no tape (MD 2.9% [95%CI: 0.8 to 5.0]) . No differences were observed in extensor carpi radialis brevis or longus muscle activity, or extension wrist angle between conditions. Interpretation: A decreased in extensor carpi ulnaris and extensor digitorum muscle activity during multidirectional elastic tape may be evidence of a deloading effect during submaximal gripping. Highlights: Small decrease in extensor digitorum activity with multidirectional elastic tape. Small decrease in extensor carpi ulnaris activity with multidirectional elastic tape. Extensor carpi radialis activity was not altered by multidirectional elastic tape. Wrist extension angle was not altered by multidirectional elastic tape.